T-lymphocyte CREB as a potential biomarker of response to antidepressant drugs - Lim, Shinn-Won; Kim, Seonwoo; Carroll, Bernard J.; Kim, Doh Kwan (The international journal of neuropsychopharmacology, 2013)
Response to drug treatment of major depression is variable and biomarkers of response are needed. Cyclic AMP response element binding protein (CREB) is considered a key mediator of antidepressant drug effect. We studied CREB in T-lymphocytes as a potential predictor of response to a selective serotonin reuptake inhibitor (SSRI) in 69 Korean depressed patients. We determined total CREB (tCREB), phosphorylated CREB (pCREB) and CRE-DNA binding using immunoblot and electrophoretic mobility shift assays, at baseline and after 6 wk treatment. Thirty-four healthy controls were also studied. The rate of response was 36 of 69 cases (52%). Baseline levels of tCREB and pCREB were lower in the total depressed group compared to controls (p = 0.044 and p<0.001, respectively). Baseline tCREB values in responders were significantly reduced in comparison to non-responders and to controls. After 6 wk treatment, median values of change of all CREB measures were greater in responders (36) than in non-responders (33; p<0.001 for tCREB, p = 0.003 for pCREB, and p=0.072 for CRE-DNA binding). Similar but less robust changes in CREB variables distinguished remitters from non-remitters. The optimum value of baseline tCREB predicted response with a positive predicted value of 0.778 [21/27; 95% confidence intervals (CI) 0.621–0.935], negative predictive value of 0.643 (27/42; 95% CI 0.498–0.788) and accuracy of 0.695 (48/69; 95% CI 0.586–0.804). Patients with low baseline tCREB had a significantly greater rate of response (78%) than patients with high baseline tCREB (36%), p < 0.001. Moreover, the greatest changes in tCREB with treatment were observed in subjects who did respond. This preliminary study suggests that T-lymphocytic CREB biomarkers are reduced in depressed patients and may assist in the prediction of response to SSRI drugs in depression.